Online Physical Education Learning During Post-Pandemic Education: Challenges And Opportunities - Agil Hagaini Hulu; Nurul Ikhwani (Journal of Global Educational Perspectives, 2026)
The transition to online learning during the COVID-19 pandemic has significantly impacted the implementation of Physical Education (PE), a subject traditionally dependent on direct physical interaction and practical activities. This study aims to explore the challenges and opportunities of online Physical Education learning in the post-pandemic era. Using a qualitative research design, data were collected through interviews, observations, and document analysis involving Physical Education teachers and students at the secondary school level. The findings indicate that major challenges include limited physical space, difficulties in assessing student performance, low student motivation, and unequal access to technology. However, the integration of digital tools and the adoption of hybrid learning models provide new opportunities to enhance flexibility, promote personalized learning, and encourage lifelong physical activity. The study also highlights the importance of teacher digital competence and institutional support in ensuring effective implementation. In conclusion, while online Physical Education presents notable limitations, it also offers innovative pathways for improving teaching and learning practices in the post-pandemic educational landscape